LINGOCULTURAL INTERPRETATION OF LEXEMES DENOTING HOUSEHOLD ITEMS IN ENGLISH AND UZBEK LANGUAGES - Narmurodova Gulnoza Ilhom Kizi (Western European Studies, 2025)
The names of household items, which serve as a rich source for studying specific aspects of national mentality, were analyzed in English and Uzbek from linguistic and linguocultural perspectives. The analysis focused on how these names reflect the peculiarities of lacunae, realities, and symbols that are part of linguocultural units
Keywords: linguoculturology; mythogems